2010
DOI: 10.1039/c004910g
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic perfusion system for maintaining viable heart tissue with real-time electrochemical monitoring of reactive oxygen species

Abstract: A microfluidic device has been developed to maintain viable heart tissue samples in a biomimetic microenvironment. This device allows rat or human heart tissue to be studied under pseudo in vivo conditions. Effluent levels of lactate dehydrogenase and hydrogen peroxide were used as markers of damaged tissue in combination with in situ electrochemical measurement of the release of reactive oxygen species (ROS). The parameters for perfusion were optimized to maintain biopsies of rat right ventricular or human ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 33 publications
3
53
0
Order By: Relevance
“…With minor alterations to the device, we have already demonstrated that liver and cardiac tissues of similar size to the malignant biopsies can be maintained and studied; the latter being electrically stimulated. 6,13 The benefit of explant-based microfluidics other than allowing the replication of the in vivo microenvironment is that it also permits numerous analyses to be undertaken on a single biopsy over several days.…”
Section: Discussionmentioning
confidence: 99%
“…With minor alterations to the device, we have already demonstrated that liver and cardiac tissues of similar size to the malignant biopsies can be maintained and studied; the latter being electrically stimulated. 6,13 The benefit of explant-based microfluidics other than allowing the replication of the in vivo microenvironment is that it also permits numerous analyses to be undertaken on a single biopsy over several days.…”
Section: Discussionmentioning
confidence: 99%
“…The test on tissue biopsy in the microfluidic device was reported by Cheah et al (Cheah et al, 2010). They developed a microsystem to maintain viable and functioning heart tissue samples in a biomimetic microenvironment.…”
Section: Heart Tissue Culture and Toxicity Analysismentioning
confidence: 96%
“…The next stage of microfluidic cardiac models is the development of 3D cell culture and biopsy analysis (Cheah et al, 2010, Khandemhosseini et al, 2007. The test on tissue biopsy in the microfluidic device was reported by Cheah et al (Cheah et al, 2010).…”
Section: Heart Tissue Culture and Toxicity Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Microscale devices with gas control and oxygen monitoring functionalities have also been used for culturing cardiac tissue and physical stimulation of cardiomyocyte contractile function 43 . Those cardiac model systems have been used for assaying loss of membrane potential and cytochrome C release as an early manifestation of apoptosis typically observed following ischemia reperfusion.…”
Section: D On-chip Technologiesmentioning
confidence: 99%